Zur Identität von Earomyia bazini (Séguy, 1932) und Earomyia connexa (Séguy, 1934) und ihren Synonymieverhältnissen (Diptera: Lonchaeidae). - Morge, Günter (Contributions to Entomology = Beiträge zur Entomologie, 1963)
After a revision of the type specimens of Earomyia bazini (Séguy) and Earomyia connexa (Séguy) the author has selected and designated lectotypes of both the species. As result of it connexa Séguy and toms kens is Morge are considered to be junior synonyms of bazini Séguy.Nomenclatural Actsbazini (Séguy, 1932) (Earomyia), Lectotype described as Lonchaea bazzinitomskensis Morge, 1959 (Earomyia), syn. n. of Earomyia bazini (Séguy, 1932)connexa Séguy, 1948 (Lonchaea), Lectotype; syn. n. of Earomyia bazini (Séguy, 1932)